Co@NCNTs / polyacrylonitrile coaxial electrospinning nanofiber membrane, preparation method and application thereof

CN122833783APending Publication Date: 2026-09-29RES INST OF XIHUA UNIV YIBIN +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611093832.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

但是,其催化剂是随机分布在纤维膜内,容易团聚,而团聚体的存在会形成应力集中点,致使纤维膜脆性断裂

Benefits of technology

本发明通过同轴静电纺丝技术构建核壳结构纳米纤维膜,将高催化活性的Co@NCNTs复合材料选择性地分布于纤维壳层,既保证了活性物质与外部环境充分接触,使催化活性位点得以高效利用,又避免了活性组分在纤维内部被过度包埋而失效,实现了活性物质利用率的最大化。同时可以让Co@NCNTs在壳层中实现高度有序排列,改善材料的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122833783A_ABST
    Figure CN122833783A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of nanofiber membrane materials, and specifically discloses a Co@NCNTs / polyacrylonitrile coaxial electrospinning nanofiber membrane, wherein the nanofiber membrane is prepared through coaxial electrospinning and has a core-shell structure; the core layer raw material comprises polyvinylpyrrolidone; and the shell layer raw material comprises Co@NCNTs, polyacrylonitrile and polyvinylpyrrolidone. In the application, the Co@NCNTs are encapsulated in the fiber shell layer, the agglomeration and loss of active components are effectively avoided, the Co@NCNTs are directionally distributed in the shell layer, and the mechanical properties of the fiber membrane are improved. The obtained fiber membrane has the advantages of large specific surface area, good electrical conductivity, rich and uniformly distributed catalytic active sites and good mechanical properties, and can be widely applied to the fields of catalytic degradation, electrochemical energy storage and water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanofiber membrane materials technology, and specifically discloses a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane, its preparation method, and its application. Background Technology

[0002] Metal-organic framework (MOF)-derived carbon-based nanocomposites have shown broad application prospects in electrocatalysis, supercapacitors, lithium-ion batteries, and wastewater treatment due to their high specific surface area, tunable pore structure, and excellent electrical conductivity. Although Co-MOFs have high specific surface area and abundant cobalt active sites, their poor electrical conductivity and insufficient chemical stability make them difficult to use directly in efficient catalytic reactions. Furthermore, their powder form presents inherent defects such as easy agglomeration, difficulty in recycling, and poor processability, which severely restrict their large-scale application.

[0003] Electrospinning, as an effective method for the continuous preparation of nanofibers, can composite functional nanomaterials with polymer matrices to obtain fibrous membrane materials with high specific surface area, good flexibility, and processability. Currently, nanofillers are typically directly incorporated into the spinning solution for uniaxial electrospinning to form films. However, this often results in extensive embedding of the filler, leading to low utilization of the nanofiller. To expose active sites, pore-forming agents are added or selective dissolution is used to create pores. While this can partially improve filler accessibility, the introduction of pores disrupts the continuity of the fiber matrix, resulting in a significant decrease in mechanical strength. Therefore, uniaxial spinning and pore-forming cannot overcome the fundamental contradiction between filler activity exposure and fiber structural integrity.

[0004] CN116926784A discloses a method for preparing and applying a composite nanofiber membrane based on a photothermal enhanced uranium ion selective adsorption-photocatalytic cascade mechanism. This patent employs a coaxial electrospinning method combined with a sacrificial template method. By constructing a hollow structure, the fiber wall thickness is reduced to a level matching the catalyst size, thereby increasing the catalyst interface exposure rate and effectively resolving the contradiction between catalyst interface exposure and fiber structural integrity. However, the catalyst is randomly distributed within the fiber membrane, making it prone to agglomeration. The presence of agglomerates creates stress concentration points, leading to brittle fracture of the fiber membrane. Summary of the Invention

[0005] This invention provides a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane, its preparation method, and its applications. The fiber membrane has excellent hydrophilicity and antifouling properties, oil-water separation, catalytic degradation performance, and cycle stability. It can be widely used in fields such as Fenton-like catalytic degradation of organic pollutants, electrochemical oxygen / hydrogen evolution reactions, supercapacitor electrode materials, and oil-water separation filtration materials.

[0006] This invention provides the following technical solution: A Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane is provided. The nanofiber membrane is prepared by coaxial electrospinning and has a core-shell structure. The core layer material includes polyvinylpyrrolidone, and the shell layer material includes Co@NCNTs, polyacrylonitrile, and polyvinylpyrrolidone.

[0007] A method for preparing a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane includes the following steps: S1. Co-MOF was mixed with melamine and calcined in an inert atmosphere to obtain Co@NCNTs; S2. Dissolve polyvinylpyrrolidone in N,N-dimethylformamide to obtain a core spinning solution; Co@NCNTs were dispersed in N,N-dimethylformamide, and polyacrylonitrile and polyvinylpyrrolidone were added to obtain the shell spinning solution; S3. The core spinning solution and the shell spinning solution are coaxially electrospun to obtain a nanofiber membrane.

[0008] Application of a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane in catalytic degradation of organic pollutants, electrochemical energy storage electrode material, or oil-water separation material.

[0009] The design concept of this invention is as follows: Due to its poor conductivity and insufficient chemical stability, Co-MOF is difficult to use directly in efficient catalytic reactions. Therefore, this invention uses Co-MOF as a precursor and melamine as an additional carbon / nitrogen source to generate carbon nanotube structures in situ through high-temperature pyrolysis. Cobalt nanoparticles are encapsulated in nitrogen-doped carbon nanotubes, forming a stable core-shell structure. This gives Co@NCNTs excellent conductivity, abundant nitrogen-doped active sites, and good magnetic responsiveness, which is beneficial for electron transfer and product separation during the catalytic reaction.

[0010] However, Co@NCNTs exist in the form of nanoparticles, which have inherent defects such as easy aggregation, difficulty in recycling, and lack of self-supporting ability, making them unsuitable for direct application as independent membrane materials in continuous flow water treatment processes, severely restricting their large-scale application. When Co@NCNTs are directly incorporated into the spinning solution for uniaxial electrospinning, a large number of active particles are embedded inside the fiber, preventing the active sites from being contacted and utilized by the reactants. Therefore, this invention uses pure polyvinylpyrrolidone as the core layer and Co@NCNTs and polyacrylonitrile as the shell layer to prepare a high specific surface area functional nanofiber membrane with a core-shell structure. By selectively distributing the highly catalytically active Co@NCNTs in the fiber shell layer, it ensures sufficient contact between the active material and the external environment, enabling efficient utilization of the catalytic active sites, while avoiding excessive embedding and inactivation of the active components inside the fiber, thus maximizing the utilization rate of the active material.

[0011] Considering that Co@NCNTs are randomly oriented within the fiber membrane, the axial reinforcement effect cannot be effectively utilized, and stress concentration points may even form due to the presence of aggregates, leading to brittle fracture of the fiber. Therefore, this invention employs coaxial electrospinning technology. During the high-speed unidirectional stretching process of the coaxial electrospinning jet, the high aspect ratio of carbon nanotubes results in a lower orientation entropy barrier under the action of flow field shear and tensile force, making it easier for them to undergo forced directional alignment along the fiber axis. At the same time, their intrinsic conductivity generates a weak electromagnetic induction effect between adjacent carbon nanotubes, which can form a cooperative orientation behavior during the jet stretching process. Furthermore, the dipole-dipole interactions and hydrogen bonds between the carbon nanotube surface and the nitrile groups of the PAN molecular chain further exert directional traction forces at the molecular level, allowing Co@NCNTs to achieve a highly ordered arrangement in the shell, thereby improving the mechanical properties of the material and preventing brittle fracture of the fiber membrane.

[0012] The technical solution of the present invention has at least the following advantages and beneficial effects: This invention utilizes coaxial electrospinning technology to construct core-shell structured nanofiber membranes, selectively distributing highly catalytically active Co@NCNTs composite materials within the fiber shell. This ensures sufficient contact between the active material and the external environment, enabling efficient utilization of catalytically active sites, while preventing excessive embedding and deactivation of active components within the fibers, thus maximizing the utilization rate of the active material. Simultaneously, it allows for a highly ordered arrangement of Co@NCNTs within the shell, improving the material's mechanical properties.

[0013] This invention uses a pure polymer solution as the core layer, which provides excellent mechanical support to the fiber membrane and significantly improves the defect that pure powder catalysts cannot be used independently. At the same time, the shell polymer matrix plays a bonding and fixing role for Co@NCNTs, effectively preventing the agglomeration and loss of active components during use, and giving the fiber membrane good flexibility and operability, making it easy to recycle and reuse.

[0014] The Co@NCNTs composite material prepared in this invention uses Co-MOF as a precursor and melamine as an additional carbon / nitrogen source. The carbon nanotube structure is generated in situ through high-temperature pyrolysis. Cobalt nanoparticles are encapsulated in nitrogen-doped carbon nanotubes to form a stable core-shell structure. It has excellent electrical conductivity, abundant nitrogen-doped active sites and good magnetic responsiveness, which is beneficial to electron transfer and product separation in the catalytic reaction process.

[0015] This invention allows for flexible control of the catalytic activity loading of the nanofiber membrane by adjusting the amount of Co@NCNTs added to the shell spinning solution, thereby meeting the needs of different application scenarios and showing promising prospects for industrial-scale production. The resulting nanofiber membrane possesses a high specific surface area, good hydrophilicity, and a three-dimensional interconnected porous network structure, which facilitates the rapid diffusion and mass transfer of reactant molecules. It can be widely used in fields such as Fenton-like catalytic degradation of organic pollutants, electrochemical oxygen / hydrogen evolution reactions, supercapacitor electrode materials, and oil-water separation filtration materials. Attached Figure Description

[0016] Figure 1 SEM images of Co-MOF and Co@NCNTs provided in embodiments of the present invention.

[0017] Figure 2 SEM image of the Co@NCNTs-PAN nanofiber membrane provided in an embodiment of the present invention.

[0018] Figure 3 Surface elemental analysis diagram of the Co@NCNTs-PAN-20 nanofiber membrane provided in the embodiments of the present invention.

[0019] Figure 4 Infrared spectral analysis of Co-MOF, Co@NCNTs, and Co@NCNTs-PAN-X nanofiber membranes provided in the embodiments of the present invention.

[0020] Figure 5 Crystal structure analysis diagrams of Co-MOF, Co@NCNTs, and Co@NCNTs-PAN-X nanofiber membranes provided in the embodiments of the present invention.

[0021] Figure 6 The N2- adsorption-desorption curves and pore size distribution curves of Co-MOF and Co@NCNTs provided in the embodiments of the present invention are shown.

[0022] Figure 7 The N2- adsorption-desorption curves and pore size distribution curves of the Co@NCNTs-PAN nanofiber membrane provided in the embodiments of the present invention are shown.

[0023] Figure 8 The mechanical properties analysis diagram of the Co@NCNTs-PAN nanofiber membrane provided in the embodiment of the present invention is shown.

[0024] Figure 9 The diagram shows the wetting performance analysis of the Co@NCNTs-PAN nanofiber membrane provided in the embodiments of the present invention.

[0025] Figure 10This diagram illustrates the water flux and separation performance of the Co@NCNTs-PAN nanofiber membrane provided in this embodiment of the invention for different types of oily wastewater.

[0026] Figure 11 The diagram shows the separation effect of the Co@NCNTs-PAN nanofiber membrane provided in this embodiment of the invention on different emulsions.

[0027] Figure 12 The graph shows the degradation performance of the Co@NCNTs-PAN nanofiber membrane provided in this embodiment of the invention against tetracycline hydrochloride.

[0028] Figure 13 Acid-base stability analysis diagram of the Co@NCNTs-PAN-20 nanofiber membrane provided in the embodiments of the present invention. Detailed Implementation

[0029] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0030] First, the present invention provides a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane, the nanofiber membrane being prepared by coaxial electrospinning and having a core-shell structure, the core layer material including polyvinylpyrrolidone, and the shell layer material including Co@NCNTs, polyacrylonitrile and polyvinylpyrrolidone.

[0031] Second, the present invention provides a method for preparing a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane, comprising the following steps: S1. Co-MOF was mixed with melamine and calcined in an inert atmosphere to obtain Co@NCNTs; S2. Dissolve polyvinylpyrrolidone in N,N-dimethylformamide to obtain a core spinning solution; Co@NCNTs were dispersed in N,N-dimethylformamide, and polyacrylonitrile and polyvinylpyrrolidone were added to obtain the shell spinning solution; S3. The core spinning solution and the shell spinning solution are coaxially electrospun to obtain a nanofiber membrane.

[0032] The shell is made of a composite system of polyacrylonitrile (PAN) and polyvinylpyrrolidone (PVP), and one-dimensional Co@NCNTs are used as functional enhancement components to simultaneously achieve anchoring, enhancement and mass transfer.

[0033] The strongly polar nitrile groups (-C≡N) in the PAN molecular chain can form dipole-dipole interactions and hydrogen bonds with the nitrogen-doped carbon layer and residual oxygen-containing functional groups (such as -COOH, -OH) on the surface of Co@NCNTs. This allows the polymer molecular chain to tightly wrap around the surface of the active particles, achieving a strong chemical anchoring of Co@NCNTs and effectively preventing their detachment and loss during use. Simultaneously, PAN, as a fiber-forming polymer matrix, endows powder catalysts, which originally lack independent molding capabilities, with the macroscopic morphology and structural integrity of continuous fibrous membranes. Co@NCNTs, being a one-dimensional nanotube structure, also assists polyacrylonitrile in enhancing the excellent mechanical properties of the fibrous membrane.

[0034] Polyvinylpyrrolidone (PVP) has three functions in the shell: first, as a polymeric dispersant, it uses the steric hindrance effect of its long-chain structure to prevent the aggregation and sedimentation of Co@NCNTs in the spinning solution, ensuring the dispersion stability of the shell spinning solution; second, as a hydrophilic modifier, it improves the wettability of the fiber membrane surface, providing a favorable surface chemical environment for aqueous catalytic reactions and oil-water separation; and third, as a pore-forming agent, PVP partially dissolves during the subsequent water washing process, forming a mesoporous structure in the shell, further increasing the accessibility of active sites and enhancing the mass transfer and diffusion of reactant molecules.

[0035] During the high-speed uniaxial stretching process of coaxial electrospinning jet, Co@NCNTs in the shell undergo forced orientation along the fiber axis. This orientation structure has a triple reinforcement effect: first, orientation reinforcement—the one-dimensional material is orderly arranged along the direction of force, maximizing the axial load-bearing capacity; second, bridging toughening—carbon nanotubes cross the weak regions between polymer molecular chains, hindering the propagation and penetration of microcracks under external force; third, interfacial load transfer—the strong interaction between PAN nitrile groups and the surface of carbon nanotubes ensures the efficient transfer of external force from the polymer matrix to the reinforcement. The synergistic effect fully activates the axial reinforcement potential of carbon nanotubes, effectively compensating for the loss of shell mechanical properties caused by PVP addition and subsequent pore formation.

[0036] During the jet's journey to the receiving device, the shell solvent first evaporates from the outer surface, and the shell polymer concentration gradually increases from the outside in. Finally, during the solidification and shrinkage process, the Co@NCNTs particles are in situ encapsulated and tightly embedded within the shell polymer matrix, forming a semi-embedded-anchored structure. This means that most of the particle surface is tightly encapsulated by polymer molecular chains (chemical anchoring), while the outermost layer is still covered by a nanometer-thick polymer layer or partially exposed particles. This ensures the accessibility of the catalytic active sites and provides the particles with strong mechanical fixation, thus achieving a dual fixation effect of chemical anchoring and physical embedding. Combined with the mechanical locking of the three-dimensional network between fibers, the active components remain stably immobilized under repeated use and water scouring conditions.

[0037] Using water-soluble polyvinylpyrrolidone as the core layer serves several purposes: First, it acts as the inner fluid for coaxial spinning. The pure polyvinylpyrrolidone solution has moderate viscosity and excellent spinnability, ensuring continuous and stable jet ejection and forming a complete core-shell interface. Second, it serves as a mechanical load-bearing path. The core layer contains no fillers, avoiding damage to the fiber's continuity by active particles and providing fundamental mechanical support for the entire fiber membrane independent of fillers. Third, it acts as a sacrificial template for pore formation. After washing away the polyvinylpyrrolidone core layer with water following spinning, longitudinally interconnected mesoporous / macroporous channels are formed inside the fiber, significantly reducing the mass transfer resistance of reactant molecules diffusing to the active sites in the shell layer.

[0038] In this invention, one-dimensional Co@NCNTs are oriented within the shell layer, providing excellent mechanical support to the fiber membrane while stably anchoring the active components within the shell matrix. Subsequent water washing removes soluble polyvinylpyrrolidone from the core layer, forming interconnected porous channels within the fiber, further increasing the specific surface area. This allows for the full exposure of the catalytically active sites of the Co@NCNTs, effectively preventing the aggregation and loss of active components, thus achieving synergistic optimization of the fiber membrane's mechanical properties and catalytic function.

[0039] In this invention, in step S1, Co-MOF and melamine are added to ultrapure water and ultrasonically dispersed for 20-40 minutes, and then the water is evaporated at 50-70°C. The mass ratio of Co-MOF to melamine is 1:2-4.

[0040] The preparation of Co-MOF involves dissolving 6 mmol of cobalt nitrate hexahydrate and 24 mmol of 2-methylimidazole in 30 mL of methanol, mixing them, stirring at room temperature for 24 h, and then centrifuging and drying to obtain Co-MOF.

[0041] In this invention, in step S1, the calcination is carried out at 850-950℃ for 1.5-3 hours under nitrogen or argon conditions, with a heating rate of 3-8℃ / min.

[0042] In this invention, in step S1, the calcined product is washed with a sulfuric acid solution of concentration 0.3-0.8 mol / L at 30-40℃ for 1.5-3 hours. After acid washing, it is subjected to magnetic separation, water washing, and drying to obtain Co@NCNTs.

[0043] In this invention, in the core spinning solution of step S2, the mass fraction of polyvinylpyrrolidone is 15-20% based on the total weight of the core spinning solution.

[0044] In this invention, in the shell spinning solution of step S2, the mass fraction of polyacrylonitrile is 7-12% and the mass fraction of polyvinylpyrrolidone is 3-6% based on the total weight of the shell spinning solution, and the amount of Co@NCNTs added is 3-30% of the total mass of the shell spinning solution.

[0045] In this invention, during coaxial electrospinning in step S3, the positive voltage is 12.0-13.0kV, the negative voltage is -1.5~-2.5kV, the core layer injection speed is 0.08-0.12mm / min, the shell layer injection speed is 0.08-0.14mm / min, the receiving distance is 12-18cm, the receiving speed is 30-50r / min, the translation speed is 150-250mm / min, the spinning temperature is 30-40℃, the humidity is 40-55%, and the spinning time is 3-6h.

[0046] In this invention, in step S3, the membrane obtained after coaxial electrospinning is placed in ultrapure water for 1-3 hours of agitation and washing, and then dried at 50-70°C for 0.5-2 hours.

[0047] Third, this invention provides an application of Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane in catalytic degradation of organic pollutants, electrochemical energy storage electrode materials, or oil-water separation materials.

[0048] Example 1 A method for preparing a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane includes the following steps: Preparation of S1.Co@NCNTs: 6 mmol of cobalt nitrate hexahydrate and 24 mmol of 2-methylimidazole were each dissolved in 30 mL of methanol. The two solutions were mixed and reacted magnetically at room temperature for 24 h. After the reaction was completed, the product was centrifuged at 8000 r / min for 10 min, the supernatant was discarded, the precipitate was collected and dried in an oven at 60 °C for 12 h to obtain purple Co-MOF powder.

[0049] 0.8g Co-MOF and 2.4g melamine were added to 50mL of ultrapure water and ultrasonically dispersed for 30min at an ultrasonic power of 200W and a frequency of 40kHz. Then, the water was evaporated by magnetic stirring at 60℃ to obtain a uniformly mixed precursor powder.

[0050] The precursor powder was placed in a corundum boat and then placed in a tube furnace. Under a nitrogen atmosphere (nitrogen flow rate 100 mL / min), the temperature was increased from room temperature to 900 °C at a rate of 5 °C / min and held for 2 h, followed by natural cooling to room temperature. The resulting black powder was added to 50 mL of 0.5 mol / L sulfuric acid solution and acid-washed at 35 °C for 2 h to remove unstable metal species and impurities. After acid washing, the solid product was collected by magnetic separation and washed repeatedly with ultrapure water 5 times until the pH of the washing solution was neutral. The product was then dried in a vacuum drying oven at 60 °C for 12 h to obtain Co@NCNTs.

[0051] S2. Preparation of coaxial electrospinning solution: Preparation of core spinning solution: Dissolve 2g of polyvinylpyrrolidone (PVP, K30, molecular weight approximately 58,000) in 10mL of N,N-dimethylformamide (DMF, purity ≥99.5%), place in a 70℃ constant temperature magnetic stirrer, and stir at 500r / min for 8h to obtain a transparent and uniform core spinning solution.

[0052] Preparation of the shell spinning solution: 0.12 g of Co@NCNTs was added to 6 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 min (ultrasonic power 200 W, frequency 40 kHz) to ensure uniform suspension. Then, 0.6 g of polyacrylonitrile (PAN, molecular weight approximately 150,000) and 0.3 g of polyvinylpyrrolidone (PVP, K30) were added, and the mixture was stirred at 70 °C and 500 r / min for 8 h until completely dissolved, resulting in a uniformly dispersed shell spinning solution. The amount of Co@NCNTs added was 0.12 g, corresponding to a shell spinning solution mass fraction of approximately 12.2%.

[0053] S3. Preparation of nanofiber membranes by coaxial electrospinning: The core spinning solution and shell spinning solution were each injected into a 10 mL disposable syringe and mounted on a coaxial electrospinning device. The core spinning solution was connected to the inner needle (22G), and the shell spinning solution was connected to the outer needle (19G). An aluminum foil was wrapped around the receiving device as a collection substrate.

[0054] The electrospinning parameters were set as follows: positive voltage 12.5kV, negative voltage -2.0kV; core injection speed 0.090mm / min, shell injection speed 0.100mm / min; receiving distance (distance from needle to receiving plate) 15cm; receiving roller speed 40r / min; needle translation speed 200mm / min; spinning ambient temperature 35℃, relative humidity 50%; total spinning time 4h.

[0055] Under the action of a high-voltage electric field, the spinning solutions of the core layer and the shell layer are sprayed out from the coaxial needle together. After the solvent evaporates, they are deposited on the receiving roller to form a composite nanofiber membrane with a core-shell structure.

[0056] After spinning, the collected fiber membrane, along with the aluminum foil, was carefully removed and placed in a shaking cleaner. 200 mL of ultrapure water was added, and the membrane was shaken at 150 rpm for 2 hours to remove residual solvent and loosely adhered particles. After washing, the fiber membrane was removed and dried in a 60℃ forced-air drying oven for 1 hour to obtain a Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane, designated Co@NCNTs-PAN-20.

[0057] Example 2 The difference between this embodiment and Embodiment 1 is that in step S2, the amount of Co@NCNTs added is 0.03g, corresponding to a shell spinning solution mass fraction of approximately 3.3%. The remaining operating steps and process parameters are exactly the same as in Embodiment 1. The resulting product is designated Co@NCNTs-PAN-5.

[0058] Example 3 The difference between this embodiment and Embodiment 1 is that in step S2, the amount of Co@NCNTs added is 0.06g, corresponding to a shell spinning solution mass fraction of approximately 6.7%. The remaining operating steps and process parameters are exactly the same as in Embodiment 1. The resulting product is designated Co@NCNTs-PAN-10.

[0059] Example 4 The difference between this embodiment and Embodiment 1 is that in step S2, the amount of Co@NCNTs added in the shell spinning solution preparation is 0.24g, corresponding to a shell spinning solution mass fraction of approximately 24.5%. The remaining operating steps and process parameters are exactly the same as in Embodiment 1. The resulting product is designated Co@NCNTs-PAN-40.

[0060] Example 5 The difference between this embodiment and Embodiment 1 is that in step S3, the positive voltage is set to 12.0kV, the negative voltage is set to -2.5kV, the core injection rate is 0.10mm / min, and the shell injection rate is 0.12mm / min. The remaining operating steps are exactly the same as in Embodiment 1.

[0061] Example 6 The difference between this embodiment and Embodiment 1 is that the humidity of the spinning environment in step S3 is 40%, and the receiving distance is 14cm. The remaining operation steps are exactly the same as in Embodiment 1.

[0062] Experimental Example 1. The Co-MOF, Co@NCNTs and Co@NCNTs-PAN-X nanofiber membranes prepared in the examples were characterized by scanning electron microscopy (SEM). Figure 1 In the image, (a1)-(a2) are SEM images of Co-MOF, and (b1)-(b2) are SEM images of Co@NCNTs. From... Figure 1 Co-MOFs exhibit a hexahedral structure, while Co@NCNTs exhibit a slender fibrous structure.

[0063] Figure 2In the image, (A1)-(A2) are SEM images of the Co@NCNT-PAN-5 nanofiber membrane, (B1)-(B2) are SEM images of the Co@NCNT-PAN-10 nanofiber membrane, (C1)-(C2) are SEM images of the Co@NCNT-PAN-20 nanofiber membrane, and (D1)-(D2) are SEM images of the Co@NCNT-PAN-40 nanofiber membrane. Figure 2 It can be observed that the Co@NCNTs-PAN nanofiber membrane has a uniform fiber diameter and a large number of micropores on its surface. The fibers are interwoven but there is no obvious aggregation or fusion. When the amount of Co@NCNTs is increased, the diameter of the polyacrylonitrile fibers becomes thicker, and more micropores are generated.

[0064] 2. Surface EDS elemental analysis was performed on the Co@NCNTs-PAN-20 prepared in Example 1, such as... Figure 3 As shown, C, N, O, and Co elements are uniformly distributed on the surface of the nanofiber membrane, indicating that Co@NCNT is uniformly dispersed in the membrane. The cobalt element peak intensity is low. The reason for this result is that some Co is encapsulated inside the fibers or nanotubes, resulting in low element peak intensity and low content in the scanned images.

[0065] 3. The nanofiber membranes prepared in the examples were characterized by infrared spectroscopy. Figure 4 In the figures, (a) shows the infrared characterization of Co-MOF and Co-NCT, and (b) shows the infrared characterization of the nanofiber membranes of Examples 1-4. Figure 4 As shown, the Co-O, Co-N, and graphitic carbon structures of Co@CNTs and the C≡N characteristic peaks of PAN in the membrane at different preparation stages can be observed. A significant increase in Co@CNTs can also be observed, with peaks at 800-400 cm⁻¹. -1 The strength of the Co functional groups increases. XRD analysis was performed on the nanofiber membrane prepared in Example 4, as shown... Figure 5 As shown, the XRD pattern of the Co@NCNTs-PAN-40 membrane clearly shows the diffraction peaks of Co@CNTs and the characteristic diffraction angle of PAN. This indicates that Co@NCNTs-PAN nanofiber membranes were successfully prepared in Examples 1-4.

[0066] 4. The specific surface area and mechanical properties of the Co-MOF, Co@NCNTs and Co@NCNTs-PAN-X nanofiber membranes prepared in the examples were analyzed.

[0067] Figure 6 In the figure, (a)-(b) show the N2- adsorption-desorption curves and pore size distribution curves of Co-MOF, respectively, and (c)-(d) show the N2- adsorption-desorption curves and pore size distribution curves of Co@NCNTs, respectively. Figure 6As can be seen, Co@NCNTs still have a high specific surface area.

[0068] Figure 7 In the figures, (a)-(b) represent the N2- adsorption-desorption curves and pore size distribution curves of the Co@NCNT-PAN-5 nanofiber membrane, (c)-(d) represent the N2- adsorption-desorption curves and pore size distribution curves of the Co@NCNT-PAN-10 nanofiber membrane, (e)-(f) represent the N2- adsorption-desorption curves and pore size distribution curves of the Co@NCNT-PAN-20 nanofiber membrane, and (g)-(h) represent the N2- adsorption-desorption curves and pore size distribution curves of the Co@NCNT-PAN-40 nanofiber membrane. Figure 7 As can be seen, the specific surface area of ​​the Co@NCNTs-PAN-X nanofiber membrane increases with increasing Co@NCNTs content. The average pore size of the Co@NCNTs-PAN-5 membrane is 2.5 nm, that of the Co@NCNTs-PAN-10 membrane is 114.4 nm, that of the Co@NCNTs-PAN-20 membrane is 125.5 nm, and that of the Co@NCNTs-PAN-40 membrane is 135.2 nm. This indicates that the pore size of the nanofiber membrane gradually increases with the addition of carbon nanotubes, suggesting that increasing Co@NCNTs is beneficial to improving the pore structure of the nanofiber membrane.

[0069] Figure 8 In the diagram, (a) shows the stress-strain diagram of the nanofiber membranes prepared in Examples 1-4, and (b) shows the Young's modulus and tensile breaking force diagram of the nanofiber membranes prepared in Examples 1-4. Figure 8 As can be seen, the addition of Co@NCNTs significantly improves the mechanical properties of the membrane. The nanofiber membrane with 0.12g of Co@NCNTs exhibits the highest strength, reaching a tensile strength of 15.43 MPa. However, excessive addition reduces the mechanical properties of the membrane, which may be related to the aggregation of nanomaterials. A comparison of Young's modulus reveals that the Young's modulus after adding nanotubes is not significantly different, reaching a maximum of 12.2 MPa.

[0070] 5. The surface wettability of the nanofiber membrane prepared in Example 1 was analyzed, such as... Figure 9 As shown, (a) represents the water contact angle and the oil contact angle, and (b) represents the underwater oil contact angle for different oils. The comparison revealed that adding Co@NCNTs did not significantly affect the hydrophilicity; the membrane surface exhibited overall hydrophilic characteristics. Furthermore, due to the influence of PVP and Co@NCNTs, the nanofiber membrane possessed underwater superoleophobic properties.

[0071] 6. The separation performance of the nanofiber membranes prepared in the examples was analyzed. Figure 10In the figures, (a) represents the water flux of nanofiber membranes with different Co@NCNT addition amounts, (b) represents the separation performance of the Co@NCNT-PAN-40 membrane for four oil-water emulsions, (c) represents the separation performance of the Co@NCNT-PAN-40 membrane for cyclohexane emulsions containing different concentrations of SDS, and (d) represents the separation performance of the Co@NCNT-PAN-40 membrane for cyclohexane emulsions containing different surfactants. Figure 10 As can be seen, the nanofiber membrane can achieve efficient separation of emulsions with different oils, different surfactants, and different surfactant concentrations.

[0072] Figure 11 In the image, (a1-a4) demonstrates the separation effect of the Co@NCNT-PAN-40 membrane on four types of oil-water emulsions; (b1-b4) demonstrates the separation effect of the Co@NCNT-PAN-40 membrane on cyclohexane emulsions containing different concentrations of SDS; (c1-c3) demonstrates the separation effect of the Co@NCNT-PAN-40 membrane on cyclohexane emulsions containing different surfactants, with the left side showing the emulsion before separation and the right side showing the emulsion after separation. Figure 11 It can be observed that the nanofiber membrane has a good separation effect on emulsions of cyclohexane, diesel, petroleum ether, and n-hexane.

[0073] 7. The catalytic performance of the Co@NCNTs-PAN nanofiber membrane prepared in the example was analyzed, and the target pollutant degraded was tetracycline. Figure 12 In the figure, (a1) represents the degradation rate of tetracycline hydrochloride by membranes with different Co@NCNTs contents; (a2) represents the degradation rate of tetracycline hydrochloride by Co@NCNT-PAN-40 nanofiber membranes with different concentrations; and (a3) ​​represents the degradation rate of tetracycline hydrochloride by Co@NCNT-PAN-40 membranes with different PMS concentrations. Figure 12 As can be seen, the higher the Co@NCNTs content, the better the catalytic performance; as the tetracycline concentration increases, the catalytic degradation ability of the membrane weakens; at the same time, as the persulfate (PMS) concentration increases, the catalytic rate of the nanofiber membrane is enhanced.

[0074] 8. The Co@NCNTs-PAN nanofiber membrane prepared in the examples was subjected to acid, alkali, and salt stability tests, such as... Figure 13 As shown, (a) are photos of the Co@NCNT-PAN-40 membrane before and after immersion in different pH values ​​for 48 hours. (b) is the water contact angle of the membrane after immersion. It can be concluded that the appearance and surface wettability of the Co@NCNTs-PAN nanofiber membrane did not change after 48 hours in a corrosive environment, proving that it has good application environment.

[0075] In summary, the Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane of the present invention has the advantages of simple preparation, good stability and mechanical properties, pore structure, hydrophilic-oceanic oleophobic properties, excellent oil-water separation performance, and high efficiency in catalytic degradation of pollutants, which is conducive to large-scale industrial production.

[0076] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane, characterized in that, The nanofiber membrane is prepared by coaxial electrospinning and has a core-shell structure. The core material includes polyvinylpyrrolidone, and the shell material includes Co@NCNTs, polyacrylonitrile, and polyvinylpyrrolidone.

2. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 1, characterized in that, Includes the following steps: S1. Co-MOF was mixed with melamine and calcined in an inert atmosphere to obtain Co@NCNTs; S2. Dissolve polyvinylpyrrolidone in an organic solvent to obtain a core spinning solution; Co@NCNTs were dispersed in an organic solvent, and polyacrylonitrile and polyvinylpyrrolidone were added to obtain a shell spinning solution. S3. The core spinning solution and the shell spinning solution are coaxially electrospun to obtain a nanofiber membrane.

3. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 2, characterized in that, In step S1, Co-MOF and melamine are added to ultrapure water and ultrasonically dispersed for 20-40 minutes, and then the water is evaporated at 50-70℃. The mass ratio of Co-MOF to melamine is 1:2-4.

4. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 2, characterized in that, In step S1, the calcination is carried out at 850-950℃ for 1.5-3 hours under nitrogen or argon conditions, with a heating rate of 3-8℃ / min.

5. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 2, characterized in that, In step S1, the calcined product is washed with a sulfuric acid solution of concentration 0.3-0.8 mol / L at 30-40℃ for 1.5-3 hours. After acid washing, it is subjected to magnetic separation, water washing and drying to obtain Co@NCNTs.

6. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 2, characterized in that, In step S2, the mass fraction of polyvinylpyrrolidone in the core spinning solution is 15-20% based on the total weight of the core spinning solution.

7. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 2, characterized in that, In the shell spinning solution of step S2, the mass fraction of polyacrylonitrile is 7-12% and the mass fraction of polyvinylpyrrolidone is 3-6% based on the total weight of the shell spinning solution. The amount of Co@NCNTs added is 3-30% of the total mass of the shell spinning solution.

8. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 2, characterized in that, In step S3, during coaxial electrospinning, the positive voltage is 12.0-13.0kV, the negative voltage is -1.5~-2.5kV, the core layer injection speed is 0.08-0.12mm / min, the shell layer injection speed is 0.08-0.14mm / min, the receiving distance is 12-18cm, the receiving speed is 30-50r / min, the translation speed is 150-250mm / min, the spinning temperature is 30-40℃, the humidity is 40-55%, and the spinning time is 3-6h.

9. The method for preparing Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 2, characterized in that, In step S3, the membrane obtained after coaxial electrospinning is placed in ultrapure water and shaken for 1-3 hours, and then dried at 50-70℃ for 0.5-2 hours.

10. The application of the Co@NCNTs / polyacrylonitrile coaxial electrospun nanofiber membrane according to claim 1 in the catalytic degradation of organic pollutants, electrochemical energy storage electrode material or oil-water separation material.